UV irradiation effect on paramagnetic properties of nanomagnetite doped with Ag(I) and Au(III) cations - O. M. Lavrynenko; M. N. Zahornyi; M. M. Bataiev; Yu. M. Bataiev; O. Yu. Pavlenko; O. A. Kornienko (Хімія, фізика та технологія поверхні)
Nowadays nanocomposites based on magnetite doped with noble metal cations or core&shell type nanocomposites including superparamagnetic core and precious metal shells are widely used in new kinds of biocompatible materials creation. The following structures are characterized by unique complexes of physical-chemical properties. The noble metal coatings formed on the magnetite nanoparticles surface supply their corrosive biological media stabilization and effects on electrical, magnetic, catalytic, optical properties of core&shell type nanocomposites as well. This work studies the effect of UV irradiation (253 nm) on the paramagnetic characteristics of biocompatible core&shell type nanocomposites based on magnetite and precious metals (silver, gold). Nanoparticles of magnetite and core&shell type composites Fe3O4&Ag0 and Fe3O4&Au0 were formed under the rotation-corrosion dispergation conditions on the steel 3 (St3) surface contacting with distilled water and aqueous solutions of silver nitrate and tetrachloroauric acid at a free flow of oxygen into the reaction zone. Solutions of precious metals contained from 0.5 to 20 mg/dm3 of Ag(I) and Au(III) aquaforms. The composite nanoparticles were characterized using X-ray diffraction data, scanning electron microscopy and electron paramagnetic resonance spectroscopy. Because of expecting photocatalytic activity of as-prepared nanocomposites, we performed their illumination by ultraviolet irradiation. The effect of UV irradiation (253 nm) on the paramagnetic characteristics of biocompatible core&shell nanocomposites based on magnetite and precious metals (silver, gold) was studied by EPR analysis. The obtained data suggests that after UV irradiation the contribution of Fe2+ spins increases, the band gap for Fe3O4 decreases, the rate of charge redistribution at the oxide-metal interface increases, the number of spins in the composite increases. The study of the occurrence of paramagnetic centers mechanism in the nanocomposites based on magnetite and precious metals may be relevant for determining their bactericidal and photocatalytic activity. Also, such nanocomposites can be used in the creation of technical means for prevention of the spread of infectious diseases in the transport, public places, and hospitals.